Relationship Between Environmental Sanitation and Incidence of Diarrhea in Under-Frees in The Working Area of The Bandar Marsilam Puskesmas, Simalungun District - Romauli Pakpahan (Institute of Computer Science (IOCS), 2022)
Diarrhea is still a health problem and a cause of death among toddlers where environmental sanitation is not proper can increase cases of diarrhea. The purpose of this study was to determine the relationship between sanitation , environment and diarrhea in toddlers at the Bandar Marsilam Health Center, Simalungun Regency. The research method used in this research is | Obscrvational with cross sectional approach. The subject of this research is ib 1 | households with children and their children experienced a diarc from 3 months June to December 2009 with a population of 328 children. Samples were selected using simple random sampling technique. There were 60 housewives involved in this study. The Chi sguare test was used to analyze the data. The results showed that there was a relationship between the source of drinking water (P 0.001), toilet ownership (P - 0.018), floor type of house (P - 0.036) cases of diarrhea in toddlers. There is no relationship between the physical quality of water (V 0.307) and cases of diarrhea in toddlers.